Evapotranspiration loss of water from rice and wheat plants grown in sand and sandy soil in bottom closed earthen pots under gravity irrigation system (Bangladesh Journal of Scientific Research, 2016)
Abstract not availableBangladesh J. Sci. Res. 28(2): 181-184, Dec-2015